2023
DOI: 10.3389/frph.2023.1089104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of unintended pregnancy and associated factors among adolescent girls and young women at risk of HIV infection in Kampala, Uganda

Abstract: BackgroundIn sub-Saharan Africa, one in every five young women becomes pregnant, and 50% of these are unintended. Pregnancies in adolescent girls and young women (AGYW) are associated with poorer maternal and neonatal outcomes and a high abortion rate, yet data are still limited on incident pregnancies among AGYW in vulnerable situations. We studied the incidence and factors associated with unintended pregnancy among AGYW who were frequently engaged in transactional sex in Kampala, Uganda.MethodsWe analyzed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Furthermore, antenatal care services may not be youth-friendly, and the approach taken by health professionals toward adults aged 18-24 may be discouraging, which reduces their utilization of the services. Related to the results, Namukisa et al [25] indicated that maternal young age is associated with lower rates of ANC usage due to many young women having unwanted pregnancies. Contrary to the above results, [26] found that young women (below 25 years) were more likely to receive antenatal care than older women (above 31 years).…”
Section: Health Facility Related Factors Associated With Delayed Util...mentioning
confidence: 87%
“…Furthermore, antenatal care services may not be youth-friendly, and the approach taken by health professionals toward adults aged 18-24 may be discouraging, which reduces their utilization of the services. Related to the results, Namukisa et al [25] indicated that maternal young age is associated with lower rates of ANC usage due to many young women having unwanted pregnancies. Contrary to the above results, [26] found that young women (below 25 years) were more likely to receive antenatal care than older women (above 31 years).…”
Section: Health Facility Related Factors Associated With Delayed Util...mentioning
confidence: 87%
“…Similarly, in Ethiopia, sexual debut before the age of 18 was positively associated with unintended pregnancies [ 63 ]. Adolescents during this period of rapid physical development may be particularly vulnerable to exploitation by older individuals due to ignorance about their own physical and sexual development [ 17 , 32 , 33 ]. Encouraging adolescents to abstain from sexual activity during this critical period can help delay the onset of sexual activity and reduce the likelihood of unintended pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…This includes being further stigmatised by healthcare staff who openly question youth about whether their sexual activities are age appropriate. Stigma is also noted by numerous studies to be a universal issue affecting individuals in all areas of their lives and is shown to affect healthcare-seeking behaviour [ 23 ], [ 24 ]. Context-specific innovative programs, example mastery experiences through sport which will also include vicarious experiences whereby youth observe peers succeeding at certain sports, are needed to build up self-efficacy and resilience within youth themselves which could then empower them to deal with experiences of stigma more effectively.…”
Section: Discussionmentioning
confidence: 99%